EFFECTIVENESS OF GIVING WATER TEPID SPONGE AGAINST HYPERTHERMIA POST PENTABIO IMMUNIZATION AT POSYANDU LUWUK VILLAGE, PASURUAN DISTRICT - Mubarok, Siti Fitriyatul; Widiatrilupi, Raden Maria Veronika; Alfitri, Rosyidah (Indonesian Journal for Health Sciences, 2024)
Children who are given Pentabio immunization often experience an increase in body temperature 37.5°C, this is called Hyperthermia. One therapy to overcome hyperthermia is Water Tepid Sponge. This study aims to determine the effectiveness of giving Water Tepid Sponge on Hyperthermia after Pentabio Immunization in Luwuk Village, Pasuruan Regency. The design of this study used Pre-Experimental with the One-Group Pre-test and Post-test Design approach. The research sample was 17 respondents with water-tepid sponge intervention every 30 minutes for 90 minutes. The researcher used an instrument in the form of a body temperature observation sheet. The sampling technique used was purposive sampling and bivariate analysis using the Friedman Test. The results of the study showed that there was effectiveness in giving Water Tepid Sponge on reducing body temperature of hyperthermia in infants after Pentabio immunization. Judging from the results of the Friedman Test analysis, a p-value of 0.000 0.05 was obtained with an average decrease in body temperature before and after of 1.60°C in 90 minutes of intervention. The study concludes that there is effectiveness in administering a Water Tepid Sponge to reduce hyperthermia body temperature in infants after pentabio immunization